The combination of natural heritage and rural tourism for local development - Izábal de la Garza, Evelia de Jesus (2025)
Given the detriment to economic activities that once supported rural communities, there is a need to identify new alternatives that will enable them to survive, grow and develop in ways that contribute to local development. This study analysed the process by which the community of Surutato, Badiraguato, located in the state of Sinaloa, Mexico, is moving towards tourism through the exploitation of its natural heritage. The research was primarily qualitative, with information collected through observation and a series of interviews with key actors from Surutato. The findings showed that the natural heritage of Surutato contributed to the spontaneous development of tourism, which was later promoted by local ejidatarios. Entrepreneurs in Surutato are currently meeting to design strategies to attract more tourism. It was concluded that the government is one of the leading actors in generating public policies related to tourism, which, together with entrepreneurs and the population, has bet on the sector, allowing it to position itself as a key economic activity. Coordination among these actors is recommended to monitor and evaluate their implementation, thereby avoiding degradation of the natural heritage that supports such activity.